IoT & Digital Twins Concept Integration Effects on Supply Chain Strategy: Challenges and Effects - Simchenko, N.A.; Tsohla, S.Y.; Chyvatkin, P.P. (International Journal of Supply Chain Management, 2019)
IoT is set to revolutionize the supply chainÃ¢â‚¬â€both in terms of its operational efficiencies and revenue opportunitiesÃ¢â‚¬â€by making it transparent. This paper is devoted to the investigation of the challenges and effects of IoT and Digital Twins integration. The goal is to ensure the formation of a methodological basis for calculating the cumulative effect of the accelerated implementation of digital twins, which should become a source of reserved growth and increase the competitiveness of a modern industrial enterprise. Our study revealed that in the context of the modern digital transformation of industry, these concepts are mutually penetrating and complementary for two reasons: 1) Big Data being the basis of IoT implementation are not valuable in themselves, since they are characterized by the lack of systematization of huge data arrays presented in different metrics. Big Data gain value in solving specific business problems; 2) The digital transformation of industry determines the shift in the value of the assets of a company towards such a specific asset as Digital Twins. In this regard, IoT should be considered as one of the environments for creating the most valuable asset of companies in a digital economy - Digital Twins. From a methodological point of view, the integration of these concepts allows us to form several intermediate digital standardization forms within the continuum Ã¢â‚¬Å“standardization - technological breakthroughÃ¢â‚¬Â.